The modified Lunn-McNeil model in the assessment of intensity of exiting from the unemployment - Bieszk-Stolorz, Beata (Zmodyfikowany model Lunna-McNeila w ocenie intensywności wyjścia z bezrobocia, 2019)
The goal of the article is the assessment of the relative intensity of exiting from unemployment of long-term unemployed people with relation to their characteristics: gender, age, education, seniority and the number of subsequent registrations. The modified Lunn-McNeil model for various types of competing events: accepting the job, refusal and remaining causes of deregistration was used in the research. The modification consisted of the application of the stratified Cox model of non-proportional hazard, which allowed to assess the relative hazard after entering the state of long-term unemployment. The individual data of persons registered in the County [Powiat] Labour Office in Szczecin were used in the research. Age had the greatest impact on the change in relative hazard at the transition to long-term unemployment, while the level of education had no significant impact. The research made it possible to identify groups of people taking up work with the least intensity and refusing to take up jobs with the greatest intensity. These people should be taken into consideration during the process of creating the labour market policy.
Econometrics = Ekonometria, 2019, Vol. 23, No. 1, s. 77-89
Keywords: Lunn-McNeil model; non-proportional hazards; competing events; long-term unemployment; model Lunna-McNeila; model nieproporcjonalnego hazardu; zdarzenia konkurujące; długotrwałe bezrobocie